Passive Flow Control of Ahmed Body using Control Rod - AHMET ŞUMNU (International Journal of Automotive and Mechanical Engineering, 2022)
In the current study, numerical analysis of passive control flow with a control rod for Ahmed body is performed at different slant angles and velocities and placed rod locations on the slant surface. The aim of the study is to improve aerodynamic performance by preventing flow separation on the slant surface of Ahmed body using a control rod. This passive flow control method uses a control rod that has not been applied for simplified ground vehicles before. Therefore, it can be said that this study is a new example in point of a passive flow control application for Ahmed body. The solution of the study is performed by using the Computational Fluid Dynamics (CFD) method. The solutions are firstly performed for baseline geometry, and the results are compared with experimental data reported in the literature for validation. CFD solutions are carried out by means of the ANSYS and RNG k- turbulence model is used to simulate flow-field since it captures the effect of turbulent flow. The solutions used a control rod with a 20 mm diameter performed at a dimensionless location (X/L=0.057 and 0.153) for Ahmed body. The results are presented visually in the figures, and drag coefficient values are also given in Table format. It is concluded that the rod application is useful for some specified slant angles and velocities since flow separation delays and suppresses the slant surface. The maximum drag reduction is achieved at about 6.153% at a slant angle of 35° and 20 m/s velocity of air, and location of control rod of 0.057, while the minimum drag reduction is about 1.048% at slant angle of 25° and velocity of air at 40 m/s and location of control rod of 0.153.